Instilling the 5S Culture (Smile, Greet, Say Hello, Be Polite, Courteous) Through the Implementation of Amar Ma'ruf Nahi Munkar and the Exemplary Behavior of Early Childhood Educators at Al-Munawaroh Tanjung Mekar Tanjung Pura - Vina Julianti; Heny Himawan; Nia Kurnia; Anisa Desi Cahyani; Sri Wulandari (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2026)
Early Childhood Education (PAUD) is an important foundation in shaping children's character and behavior. This study aims to analyze strategies for strengthening the 5S habit in early childhood through the application of modeling techniques (exemplary behavior) as a concrete form of implementing the Amar Ma'ruf value (encouraging goodness) in the AL-MUAWAROH Tanjung Mekar Tanjung Pura PAUD environment. Early childhood is in a golden age where they are highly susceptible to imitation, making modeling techniques by teachers and adults the most effective method for instilling moral values. The 5S habit, which is an essential part of social ethics and a symbol of peace, plays a role in developing friendly, socially sensitive characters and creating a harmonious and conducive environment. The method used was qualitative, with case studies through observation, interviews, and documentation. The study results show that teachers' consistent and sincere model of the 5S, combined with positive reinforcement, can foster a friendly and socially aware character in children. This success aligns with the essence of the teachings of Amar Ma'ruf (Committing Good and Ethical Conduct) and creates an Islamic, friendly, and compassionate environment. Instilling character values ​​in early childhood at AL-MUNAWAROH is a fundamental aspect in shaping human personality. The 5S culture (Smile, Greet, Greet, Polite, and Courteous) serves as a strategic approach in developing the social, moral, and religious character of early childhood. This article aims to analyze the implementation of the 5S culture in early childhood education at AL-MUNAQAROH, integrated with the concept of amar ma'ruf nahi munkar (enjoining good and forbidding evil) through the role models of educators. The research method used a literature review with a descriptive-analytical approach. The study results indicate that consistent implementation of the 5S culture can create a positive learning environment, enhance children's social-emotional development, and instill Islamic values ​​aligned with the Independent Curriculum.